2021
DOI: 10.1186/s13722-021-00281-3
|View full text |Cite
|
Sign up to set email alerts
|

Rural opioid treatment program patient perspectives on take-home methadone policy changes during COVID-19: a qualitative thematic analysis

Abstract: Background In the United States, methadone for opioid use disorder (OUD) is highly regulated. Federal agencies announced guidelines in March 2020 allowing for relaxation of take-home methadone dispensing at opioid treatment programs (OTPs) to improve treatment access and reduce COVID-19 transmission risk during the public health emergency. We explored patient perspectives at three OTPs serving rural communities on how take-home policy changes were received and implemented and how these changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 57 publications
3
30
0
Order By: Relevance
“…The OTP had been established two years prior to the other site. These findings provide additional data on how patients adapted to COVID-19-related policy changes, the benefits and challenges with increased take-home doses, and possibilities for future directions of OTP-related regulations ( Harris et al, 2021 ; Levander, Hoffman, et al, 2021 ). Qualitative reports of continued recovery in the context of fewer restrictions suggest feasibility and desirability of enhanced access to take-homes without detrimental harm particularly in OTPs serving rural communities.…”
Section: Discussionmentioning
confidence: 90%
“…The OTP had been established two years prior to the other site. These findings provide additional data on how patients adapted to COVID-19-related policy changes, the benefits and challenges with increased take-home doses, and possibilities for future directions of OTP-related regulations ( Harris et al, 2021 ; Levander, Hoffman, et al, 2021 ). Qualitative reports of continued recovery in the context of fewer restrictions suggest feasibility and desirability of enhanced access to take-homes without detrimental harm particularly in OTPs serving rural communities.…”
Section: Discussionmentioning
confidence: 90%
“…Preliminary data highlight that those who were able to access OAT carries due to the revised policies benefitted from this change, particularly as access to carries permitted them to stabilize their routines, physically distance to reduce the risk of virus transmission, and subsequently decrease their substance use [18,64,68,[70][71][72]. For instance, in a US-based qualitative study emphasizing patient's perspectives, many individuals acknowledged significant benefits of receiving carries during COVID-19 including experiencing feelings of normalcy and stability, improvements to recovery support, and increased time with family and work-benefits which increased their self-confidence and commitment to OAT adherence [73]. Early Canadian data further indicate that most people who received additional carries were no more likely to experience adverse outcomes (e.g., self-reported opioid overdoses, emergency department visits, etc.)…”
Section: Covid-19: Special Considerations and Circumstancesmentioning
confidence: 99%
“…In terms of the regulatory changes, many countries temporarily allowed for more flexible service delivery models in the context of COVID-19, for instance, allowing clients to obtain more takeaway (take-home) doses of methadone and buprenorphine, using telemedicine for reviews and evaluations, accelerating the expansion of long-acting injectables (e.g., depot buprenorphine), delivering medications to clients where possible, extending the duration of prescriptions, and increasing access to take-home naloxone (British Columbia Centre on Substance Use, 2020; Farhoudian et al, 2020; Lintzeris et al, 2020; Substance Abuse and Mental Health Services Administration [SAMHSA], 2020). Despite some concerns around policy implementation (Becker et al, 2021; Pérez-Chiqués et al, 2021), early evaluations suggest that these regulatory changes have led to few if any unintended consequences (Brothers et al, 2021; Caton et al, 2021; Kitchen et al, 2022; Lintzeris et al, 2021; Saloner et al, 2022; Welsh et al, 2022), and clients have reported greater self-efficacy and recovery capital as a result of the increased flexibility in treatment (Levander et al, 2021). There have been calls to sustain and expand these improvements to treatment delivery beyond the pandemic (Corace et al, 2022; Durand et al, 2022; Grebely et al, 2020; Green et al, 2020), and in the US the Substance Abuse and Mental Health Services Administration have recently extended the temporary policy changes for another year, and also have plans to make them permanent (SAMHSA, 2021).…”
Section: Case Studymentioning
confidence: 99%